A clinico-pathological and follow up study of 10 cases of essential type II cryoglobulinaemic neuropathy. Issue 10 (October 1990) - Cavaletti, G; Petruccioli, M G; Crespi, V; Pioltelli, P; Marmiroli, P; Tredici, G
Abstract : Ten patients with essential cryoglobulinaemia type II were examined for peripheral nerve damage. In six cases distal symmetrical nerve involvement was present, while in three other cases abnormalities restricted to single nerves were found. Electrophysiological and morphological data were consistent with axonal damage, the larger myelinated fibres being most affected. Although active signs of vasculitis and immunoperoxidase staining for immunoglobulins were not present, endoneurial vessels were widely damaged, with abnormally thick endothelial cells and redundant basal membranes. These findings, together with a patchy distribution of myelinated fibre loss, suggest ischaemia as a cause of peripheral neuropathy during essential cryoglobulinaemia type II. A follow up examination, performed one year after haematologial remission, revealed that no further peripheral nerve damage had occurred.